Ground Improvement and Earth Structures Proceedings of the 1st GeoMEast International Congress and Exhibition, Egypt 2017 on Sustainable Civil Infrastructures (Sustainable Civil Infrastructures,, 2018)
This volume contains research articles that cover a wide range of topics related to ground improvement and subsurface structures. Selected papers represent the state-of-the-art in the analysis and design of reinforced retaining walls, diaphragm walls and buried pipes. In addition, topics related to ground improvement using vacuum consolidation and deep mixing techniques are also included. This volume is part of the proceedings of the 1st GeoMEast International Congress and Exhibition on Sustainable Civil Infrastructures, Egypt 2017.